2014
DOI: 10.31018/jans.v6i2.497
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cutting frequencies and nitrogen levels on growth, green and seed yield and quality of water spinach (Ipomoea reptans Poir.)

Abstract: Abstract:To study the effect of cutting frequencies and nitrogen levels on growth, green and seed yield and quality of upland water spinach (Ipomoea reptans Poir.) an experiment was undertaken with four cutting frequencies (C 0 = no cutting; C 1 = one cutting at 45 days after sowing (DAS); C 2 = two cutting at 45 and 65 DAS and C 3 = three cutting at 45, 65 and 85 DAS) and five nitrogen levels (N 0 = no application; N 1 = 50 kg/ha; N 2 = 100 kg/ha; N 3 = 150 kg/ha and N 4 = 200 kg/ha). Results revealed that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
3
4
0
Order By: Relevance
“…The overall genotypic mean irrespective of cutting levels observed that maximum vigour index-II (18.95) for the genotype DH-5 followed by (14.60) for the genotype DH-228 and minimum vigour index-II was recorded (8.57) for the genotype DH-36 among the genotypes. The results of seedling vigour index are in accordance with the results obtained by Phor [16] in palak and Sarkar [18] in water Spinach.…”
Section: Effect Of Foliage Cuttings On Foliage and Seed Yield Of Corisupporting
confidence: 90%
“…The overall genotypic mean irrespective of cutting levels observed that maximum vigour index-II (18.95) for the genotype DH-5 followed by (14.60) for the genotype DH-228 and minimum vigour index-II was recorded (8.57) for the genotype DH-36 among the genotypes. The results of seedling vigour index are in accordance with the results obtained by Phor [16] in palak and Sarkar [18] in water Spinach.…”
Section: Effect Of Foliage Cuttings On Foliage and Seed Yield Of Corisupporting
confidence: 90%
“…The current result showed that higher application of nitrogen rates in I. aquatica can reduce the plant stress by having lower WUE. [22]. A similar result was obtained by Artur et al [39] where the increase of N has reduced…”
Section: Water Use Efficiency (Wue)supporting
confidence: 82%
“…can reduce the plant stress by having lower WUE. [22]. A similar result was obtained by Artur et al [39] where the increase of N has reduced the WUE in Marandu grass that showed a hig application of nitrogen can reduce stress in aquatica.…”
supporting
confidence: 76%
See 2 more Smart Citations